Addition of flexible linkers to GPU-accelerated coarse-grained simulations of protein-protein docking - Pinska, Adrianna (Department of Computer Science, 2019)
Multiprotein complexes are responsible for many vital cellular functions, and understanding their formation has many applications in medical research. Computer simulation has become a valuable tool in the study of biochemical processes, but simulation of large molecular structures such as proteins on a useful scale is computationally expensive. A compromise must be made between the level of detail at which a simulation can be performed, the size of the structures which can be modelled and the time scale of the simulation. Techniques which can be used to reduce the cost of such simulations include the use of coarse-grained models and parallelisation of the code. Parallelisation has recently been made more accessible by the advent of Graphics Processing Units (GPUs), a consumer technology which has become an affordable alternative to more specialised parallel hardware. We extend an existing implementation of a Monte Carlo protein-protein docking simulation using the Kim and Hummer coarse-grained protein model [1] on a heterogeneous GPU-CPU architecture [2]. This implementation has achieved a significant speed-up over previous serial implementations as a result of the efficient parallelisation of its expensive non-bonded potential energy calculation on the GPU. Our contribution is the addition of the optional capability for modelling flexible linkers between rigid domains of a single protein. We implement additional Monte Carlo mutations to allow for movement of residues within linkers, and for movement of domains connected by a linker with respect to each other. We also add potential terms for pseudo-bonds, pseudo-angles and pseudo-torsions between residues to the potential calculation, and include additional residue pairs in the non-bonded potential sum. Our flexible linker code has been tested, validated and benchmarked. We find that the implementation is correct, and that the addition of the linkers does not significantly impact the performance of the simulation. This modification may be used to enable fast simulation of the interaction between component proteins in a multiprotein complex, in configurations which are constrained to preserve particular linkages between the proteins. We demonstrate this utility with a series of simulations of diubiquitin chains, comparing the structure of chains formed through all known linkages between two ubiquitin monomers. We find reasonable agreement between our simulated structures and experimental data on the characteristics of diubiquitin chains in solution.